Merdeka Curriculum Implementation in a Pesantren Based Vocational School - Asia Anis Sulalah; Miftahul Arifin (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Indonesia's Merdeka Curriculum (Independent Curriculum) is a national policy intended to build a more flexible, competency-oriented, and character-based education system. Implementing this policy in pesantren-based (Islamic boarding school) vocational schools is particularly demanding, since such institutions must reconcile national curriculum mandates with the religious and cultural authority of their foundations. This study examined how the Merdeka Curriculum was implemented at an Islamic-based vocational school in Bondowoso Regency, East Java, focusing on the policy's communication, resourcing, implementer disposition, and bureaucratic structure, and on the factors that supported and inhibited implementation. The study used a descriptive qualitative case study design, analyzed through George C. Edward III's policy implementation framework. Data were obtained from the principal, the curriculum vice-principal, teachers and students through participant observation, in-depth interviews, and documentation, conducted over. Data were validated through source and technique triangulation and analyzed through transcription, reduction, classification, tabulation, interpretation, and conclusion drawing. The findings show that curriculum implementation involved internal readiness-building, staged socialization, structured teacher training through the Merdeka Mengajar Platform (PMM), and classroom delivery supported by collaboratively designed teaching tools. The principal functioned as a facilitator and instructional leader, evidenced by coaching-based supervision and the formation of a dedicated Curriculum Implementation Team, consistent with a distributed leadership approach. Implementation was further adapted to the school's pesantren character, taking into account students' backgrounds and the surrounding religious community, although resource constraints and uneven teacher readiness remained as identified obstacles. The study recommends strengthening collaboration among the school, its foundation, and the Education Office; optimizing limited resources; and further developing project-based learning strategies to support the sustainability of Merdeka Curriculum implementation in faith based vocational education.